COMPARATIVE STUDY OF LEADERSHIP STYLES IN PUBLIC AND PRIVATE SECONDARY SCHOOLS IN IDO LOCAL GOVERNMENT AREA OF IBADAN, OYO STATE - Bakare, Eunice B.; Oredein , Afolakemi O. (International Journal of Research -GRANTHAALAYAH, 2021)
This study compared the leadership styles of principals dominating in both public and private secondary schools in Ido Local Government Area of Ibadan, Oyo State, and also investigated the principals’ gender differences. Leadership styles examined include: autocratic, visionary, , democratic, coaching, servant, , , , bureaucratic and digital. A descriptive research design was adopted. The population of the study consists of 26 public secondary schools and 97 registered private secondary schools. The total population of teachers in the study were 1194. Using the Taro formula, a sample size of 306 respondents were sampled of which questionnaires were administered and 305 questionnaires were retrieved and used for analysis. A self-designed questionnaire that yielded reliability coefficients of r= 0.942, 0.911, 0.924 were used for data collection. A research question and two hypotheses were used to guide the study. The findings of the study showed a significant difference in the leadership style adopted by school principals of both school types with mean =92.5 and 1149, SD= 9.712 and 11.634, while (t = 0.719; = 301, p <0.05). There is also a significant gender difference in the leadership style adopted by principals of both schools with mean =125.14 and 120.97, SD= 14.195 and 9.318 and (t= 2.909; = 301; p< 0.05). The study concluded that though there are significant differences in the leadership styles adopted by the school principals, there are no leadership styles. It is therefore recommended that; principals of both school types should blend and adopt styles that best fit the situation at hand. Thus, leadership style should be applied based on contingency.